Technical Efficiency Level of Organic Coffee and Inorganic Coffee Farming in Cilengkrang District, Bandung Regency, Indonesia - Prawira, Gunawan; Harianto, Harianto; Hadianto, Adi (Agro Bali : Agricultural Journal, 2025)
Cilengkrang District is a sub-district in West Java recognized for its potential contribution to Indonesia’s coffee productivity. However, the overall productivity of coffee farming remains relatively low due to inefficiencies in farming practices. The coffee grown in Cilengkrang consists of two types: organic and inorganic.  This research aims to analyze factors that influence coffee production and analyze the level of technical efficiency of coffee farming. The study was conducted in Cilengkrang District, Bandung Regency, chosen purposively for its significant potential to contribute to the region’s coffee productivity. The sample consisted of 34 organic farmers and 34 inorganic farmers. Data collection began in August 2023 and ended in December 2024. The Stochastic Frontier Analysis (SFA) method was used to evaluate farming efficiency. The results of the analysis show that the variables of land area, liquid organic fertilizer, urea fertilizer, and KCl fertilizer influence production. Then the variables of education level, number of family members, experience, and financing dummy influence increasing farming efficiency. The efficiency level of coffee farming is included in the inefficient category.